Why not me? eaudiobook - Kaling, Mindy (Random House Audio, 2015)
#1  NEW YORK TIMES  BESTSELLER • From the author of Is Everyone Hanging Out Without Me? and creator of The Mindy Project and Never Have I Ever comes a hilarious collection of essays  about her ongoing journey to find contentment and excitement in her adult life. “This is Kaling at the height of her power.”— USA Today In Why Not Me?, Kaling shares insightful, deeply personal stories about falling in love at work, seeking new friendships in lonely places, attempting to be the first person in history to lose weight without any behavior modification whatsoever, and believing that you have a place in Hollywood when you’re constantly reminded that no one looks like you.   In “How to Look Spectacular: A Starlet’s Confessions,” Kaling gives her tongue-in-cheek secrets for surefire on-camera beauty, (“Your natural hair color may be appropriate for your skin tone, but this isn’t the land of appropriate– this is Hollywood, baby . Out here, a dark-skinned woman’s traditional hair color is honey blonde.”) “Player” tells the story of Kaling being seduced and dumped by a female friend in L.A. (“I had been replaced by a younger model. And now they had matching bangs.”) In “Unlikely Leading Lady,” she muses on America’s fixation with the weight of actresses, (“Most women we see onscreen are either so thin that they’re walking clavicles or so huge that their only scenes involve them breaking furniture.”) And in “Soup Snakes,” Kaling spills some secrets on her relationship with her ex-boyfriend and close friend, B.J. Novak (“I will freely admit: my relationship with B.J. Novak is weird as hell.”)   Mindy turns the anxieties, the glamour, and the celebrations of her second coming-of-age into a laugh-out-loud funny collection of essays that anyone who’s ever been at a turning point in their life or career can relate to. And those who’ve never been at a turning point can skip to the parts where she talks about meeting Bradley Cooper.